1998
DOI: 10.1007/s000490050018
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic origin of carbon-based secondary compounds: cause of variable responses of woody plants to fertilization?

Abstract: We propose that variation in the responses of carbon-based secondary compounds to fertilization in woody plants has a biosynthetic cause. The synthesis of phenylpropanoids and derived compounds (e.g., condensed tannins) competes directly with the synthesis of proteins, and therefore with plant growth, because of a common precursor, phenylalanine. In contrast, the biosynthesis of terpenoids and of hydrolyzable tannins proceeds presumably without direct competition with protein synthesis. Therefore, accelerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
1
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(160 citation statements)
references
References 77 publications
4
146
1
9
Order By: Relevance
“…In most studies, phenolic production decreases at high nitrogen availability and increases under nitrogen deficiency. 30 This trend was not followed by M. cauliflora, which showed no correlation in total phenol/ tannin contents with nitrogen levels; this phenomenon has also been reported for tannins in Colophospermum mopane (J. Kirk ex Benth.) J. Léonard (Fabaceae).…”
Section: Resultsmentioning
confidence: 71%
“…In most studies, phenolic production decreases at high nitrogen availability and increases under nitrogen deficiency. 30 This trend was not followed by M. cauliflora, which showed no correlation in total phenol/ tannin contents with nitrogen levels; this phenomenon has also been reported for tannins in Colophospermum mopane (J. Kirk ex Benth.) J. Léonard (Fabaceae).…”
Section: Resultsmentioning
confidence: 71%
“…Owuor et al (1987) reported that the quality of black tea deteriorated with increased nitrogenous fertilizer ranging from 450 to 600 kg ha -1 N. The polyphenol derivatives such as theaflavins and thearubigins also decreased with increased N levels (Owuor & Odhiambo, 1994). Soil-applied N delayed the onset of tannin production, while foliar-applied urea at the time of tannin accumulation inhibited the process of tannin biosynthesis (Haukioja et al, 1998). In contrast, the results of this study showed that condensed tannins significantly decreased with higher rates of N application from 300 to 500 kg ha -1 N, probably due to a trade-off between the synthesis of phenolics and proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The protein competition model (Jones and Hartley 1999) also suggests that the regulation of protein and phenolic synthesis are tightly linked due to the use of the same precursor phenylalanine. Therefore, plant cells do not appear to be capable of simultaneously synthesising proteins and phenolics at the same rate (Haukioja et al 1998). …”
Section: Responses Of Tannins To N Supply and Light Intensitymentioning
confidence: 99%